Concurrent vaccination against equine influenza and equine herpesvirus – a practical approach. Issue 5 (2nd July 2016) - Gildea, Sarah; Sanchez Higgins, Maria Jose; Johnson, Gillian; Walsh, Cathal; Cullinane, Ann
Abstract : Background: There is a lack of information concerning concurrent administration of vaccines against equine influenza virus (EIV) and equine herpesvirus 1 and 4 (EHV‐1/4). Objectives: The primary objective of this study was to determine the impact of the concurrent use of EIV and EHV‐1/4 vaccines in Thoroughbred racehorses on their humoral immune response to EIV. Methods: This study was carried out on a population of 30 horses using an inactivated whole‐virus EIV vaccine and an inactivated EHV‐1/4 vaccine. Horses were randomly allocated to vaccination group A or B. Horses in group A were vaccinated against EIV and EHV‐1/4 2 weeks apart. Horses in group B were vaccinated against EIV and EHV‐1/4 on the same day. Whole‐blood samples were collected on the day of vaccination and 2 weeks and 6 weeks post‐vaccination. Antibody levels against EIV and EHV‐1/4 were measured using the single radial haemolysis and serum neutralisation test, respectively. Results: The pattern of EIV antibody response post‐vaccination was similar for both groups. Highest EIV antibody levels were recorded 2 weeks post‐vaccination, and a significant decrease in antibody level was observed 4 weeks later. Horses in group B demonstrated a significantly higher EIV antibody response post‐vaccination. Overall, there was no significant difference in EHV‐1/4 antibody response between the two groups post‐vaccination. Conclusion: In this study, concurrent vaccination against EIV and EHV‐1/4 increased the response to EIV and did not compromise the humoral immune response to EHV‐1/4.